2012
DOI: 10.3892/ijo.2012.1514
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virotherapy for human bone and soft tissue sarcomas using live attenuated poliovirus

Abstract: The poliovirus receptor CD155, is essential for poliovirus to infect and induce death in neural cells. Recently, CD155 has been shown to be selectively expressed on certain types of tumor cells originating from the neural crest, including malignant glioma and neuroblastoma. However, the expression pattern of CD155 in soft tissue sarcoma has not been examined. Therefore, we first examined CD155 expression in sarcoma cell lines, and found the expression of both CD155 mRNA and protein in 12 soft and bone tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Several studies have also shown that live-attenuated poliovirus induces apoptotic cell death in tumors, including gliomas (28) and neuroblastomas (29), through the interaction with CD155 in vitro and in vivo . We previously showed that live-attenuated poliovirus has the potential to treat soft tissue sarcomas expressing CD155 as a form of oncolytic virotherapy (26). We therefore suggest that soft tissue sarcomas with upregulated CD155 expression may be candidates for oncolytic virotherapy using live-attenuated poliovirus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown that live-attenuated poliovirus induces apoptotic cell death in tumors, including gliomas (28) and neuroblastomas (29), through the interaction with CD155 in vitro and in vivo . We previously showed that live-attenuated poliovirus has the potential to treat soft tissue sarcomas expressing CD155 as a form of oncolytic virotherapy (26). We therefore suggest that soft tissue sarcomas with upregulated CD155 expression may be candidates for oncolytic virotherapy using live-attenuated poliovirus.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CD155 was widely expressed in various human bone and soft tissue sarcoma cell lines (26), but there have so far been no studies describing the clinicopathological implications of CD155 in soft tissue sarcomas. The present study investigated whether the CD155 gene expression level in surgically resected human primary soft tissue sarcoma tissues has prognostic significance.…”
Section: Introductionmentioning
confidence: 99%
“…CD155 was initially identified as a receptor based on its ability to mediate the binding of poliovirus to host cells (7,8), and also known as a member of the immunoglobulin family of cell adhesion molecules (9,10). CD155 is broadly distributed at low levels on epithelial and endothelial cells in many tissues (11), but overexpressed in various carcinomas including soft tissue sarcoma (12,13), colorectal cancer (14), lung adenocarcinoma (15), melanoma (16), neuroblastoma and glioblastoma (17,18). CD155 was subsequently shown to promote GBM cell migration and focal adhesion disassembly (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these studies showed a safe yet profound anti-tumor response in JX-594 monotherapy and combination treatment groups in comparison to sorafenib alone. [79][80][81] Several strategies have been tested in reducing PV neurotoxicity: (1) use of live-attenuated poliovirus vaccines, 82 (2) delivery of engineered PV genome deficient of P1 coding region (replicons), thereby preventing the formation of new viral progenies and spread, 83 (3) A133G mutation in cis-acting replication element (CRE) and relocation of CRE to a spacer region, 84 (4) replacement of internal ribosome entry site (IRES) of PV (PVSRIPO) with that of human rhinovirus 2 (HRV2). 85 Ribonucleoprotein complex formed in PVSRIPO is incompatible with HRV2 IRES-mediated translation in normal human central nervous system, therefore, rendering the neuronal incompetence of PVSRIPO.…”
Section: Dovepressmentioning
confidence: 99%